1893 N.C. Sess. Laws 148 - (:unkn) unknown (My University, 1893)
Pub. Laws, ch. 191, §§ 1-3: That no body of men composed of more than three persons calling themselves detectives or claiming to be in the employ of any detective agency or known and designated as detectives shall go armed in this state.
Keywords: CARRY